Survey on Design and Implementation of Indoor Environment Monitoring and control system (International Journal of Engineering and Computer Science, 2018)
The ideology of the Internet of things has emerged due to the consolidation of multiple technologies. IoT devices are a part of the larger concept of  home automation, also known as domotics. The application of Internet of Things in indoor environment monitoring and control has become a major area as people paying more attention to quality of environment. Intelligent solutions are proposed by studying key technologies of IoT. The system provides a new application for IoT.